Untangling the double-edged role of emotional demands in resilience and presenteeism in B2B salespeople: The analysis of ingredients and recipes - Bağcı, Rıfgı Buğra; Gölgeci, İsmail; Gizlier, Ömer; Demirkıran, Mahmut (Elsevier, 2026)
Presenteeism amid pressing emotional demands in business-to-business (B2B) sales is a prevalent yet underexplored phenomenon. Using PLS-SEM and fsQCA, we investigate whether emotional demands foster salesperson resilience while simultaneously exacerbating voluntary and involuntary presenteeism, both directly and indirectly, under the moderating role of collaborative culture, and identify distinct causal recipes for these two forms of presenteeism. PLS-SEM analysis reveals the nexus of relationships among the ingredients of presenteeism: emotional demands enhance salesperson resilience and directly drive both voluntary and involuntary presenteeism. Salesperson resilience mediates the relationship between emotional demands and voluntary presenteeism, suggesting that resilient salespeople are more likely to engage in voluntary presenteeism. However, it neither influences involuntary presenteeism nor mediates the link between emotional demands and involuntary presenteeism, indicating that resilience may serve as a buffer against involuntary presenteeism and enhance salespeople's agency. Collaborative culture negatively moderates the impact of salesperson resilience on voluntary presenteeism but does not moderate its impact on involuntary presenteeism. Furthermore, the fsQCA analysis reveals distinct causal recipes for both forms of presenteeism, including demographic and contextual factors. These findings deepen our understanding of resilience and presenteeism in B2B sales by incorporating Job Demands-Resources theory and contributions from asymmetric causal modeling.
Keywords: Presenteeism; Salesperson resilience; Job demands-resources; Collaborative culture; Emotional demands; fi=Kansainvälinen liiketoiminta|en=International Business|